Incorporation of CdFe2O4SiO2 nanoparticles in SbPO4-ZnO-PbO glasses by melting quenching process - Orives, Juliane; Viali, Wesley R.; Magnani, Marina; Nalin, Marcelo (Eclética Química, 2018)
The development of glasses containing nanoparticles dispersed homogeneously with controlled size and optimum parameters for functionality is a challenge. Glasses in the ternary system 60SbPO4-30ZnO-10PbO containing CdFe2O4-SiO2 nanoparticles were studied. The CdFe2O4 nanoparticles were synthesized by the coprecipitation method and the average size was 3.9 nm and then, they were protected by a silica layer. The nanoparticles were mixed with the glass precursors and transformed into glasses by melt-quenching method. Thermal and structural properties were evaluated by differential scanning calorimetry, Raman spectroscopy, scanning electronic microscopy and transmission electron microscopy. While the optical properties were studied by M-Lines spectroscopy and UV-VIS spectroscopy. The glass samples obtained were completely transparent, with amber color and showed no sign of crystallization according to the techniques used. Scanning and transmission electron microscopy confirm that the methodology used for the incorporation of nanoparticles was efficient. The nanoparticle protection methodology prior to incorporation into glasses may contribute towards the development of glasses containing nanoparticles useful for magneto-optics devices.